In vivo dynamics of active edema and lethal factors during anthrax - Rougeaux, Clémence (Sci Rep, 2016)
Lethal and edema toxins are critical virulence factors of Bacillus anthracis. However, little is known about their in vivo dynamics of production during anthrax. In this study, we unraveled for the first time the in vivo kinetics of production of the toxin components EF (edema factor) and LF (lethal factor) during cutaneous infection with a wild-type toxinogenic encapsulated strain in immuno-competent mice. We stratified the asynchronous infection process into defined stages through bioluminescence imaging (BLI), while exploiting sensitive quantitative methods by measuring the enzymatic activity of LF and EF. LF was produced in high amounts, while EF amounts steadily increased during the infectious process. This led to high LF/EF ratios throughout the infection, with variations between 50 to a few thousands. In the bloodstream, the early detection of active LF and EF despite the absence of bacteria suggests that they may exert long distance effects. Infection with a strain deficient in the protective antigen toxin component enabled to address its role in the diffusion of LF and EF within the host. Our data provide a picture of the in vivo complexity of the infectious process.